Language of Resistance: Linguistic Landscape in the Protest of Kanjuruan Tragedy, Indonesia - Muassomah, Muassomah; Billah, Baedt Giri Mukhoddam; Faisol, M.; Halimi, Halimi (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2024)
PurposeLinguistics landscape (LL) is not only a means of showing the identity of a language but also a constructive effort to fight for justice for society. Landscape in this study is a form of protest against security forces for the loss of life of 135 Aremania fans after watching a soccer match between Arema and Persebaya at the Kanjuruan stadium. This research aims, apart from mapping all signs from aspects of language use patterns, also to conduct a critical analysis of the language used. MethodThis study uses quantitative and qualitative methods based on documentation in the form of billboards, boards, and banners installed in various parts of Malang, Indonesia. Content analysis and critical analysis are used to analyze this research. Results/findingsThe findings of this study show that the language used in the landscape has two forms, monolingual and bilingual. In addition, it indicates that four languages are used in the sign. Indonesian has a higher quantity than English, Javanese, and Arabic. ConclusionThe language pattern used in the landscape tends to reflect sarcasm, cynicism, and rhetoric. This research suggests conducting a follow-up study that examines the same sign in the broader area, including Malang district and East Java region, to obtain varied data and various sign patterns. Thus the data information obtained is more comprehensive.